The Importance of Judo Exercise for the Development of Child's Motor Competences - Jurij Planinšec; Uroš Kavčič; Črtomir Matejek (University of Maribor Press, 2016)
The main aim of this research was to find out whether there are any differences in motor competences between children involved in judo training and their peers that are not involved in any sport. The aim of this research was also to determine whether there are any differences in anthropometric measurements. For this purpose, we conducted an educational experiment. The research was based on non-random (convenience) sampling that included 54 boys divided into experimental and control group. In the experimental group there were 27 pupils of the first, the second and the third grade of basic school that train judo in JK Murska Sobota and in the control group there were 27 pupils attending the first, the second and the third grade. Apart from the regular Physical Education classes at school the boys in the control group were not involved in any kind of organised sport activities. Both groups were tested before and after a three-month training period. For statistical analyses the analysis of covariance was used. The findings showed that the experimental group was better in most of the physical fitness tests, while in the anthropometric measurements the differences were not statistically significant. The largest differences were found in the endurance torso power, the explosive leg power, in the aerobic endurance and in the whole body coordination. Slightly smaller differences were shown only in the flexibility and balance. It can be concluded that judo training is important for the development of motor competences in children.